Alcohol-mediated Reduction of Biomass-derived Furanic Aldehydes via Catalytic Hydrogen Transfer - Xu, Yufei; Long, Jingxuan; He, Jian; Li, Hu (Current Organic Chemistry, 2019)
With the depletion of fossil energy, liquid biofuels are becoming one of the effective alternatives to replace fossil fuels. The catalytic transfer and hydrogenation of biomass-based furanic compounds into fuels and value-added chemicals has become a spotlight in this field. Gas hydrogen is often used as the H-donor for the hydrogenation reactions. It is a very straightforward and simple method to implement, but sometimes it comes with the danger of operation and the difficulty of regulation. In recent years, diverse liquid hydrogen donor reagents have been employed in the catalytic transfer hydrogenation (CTH) of biomass. Amongst those H-donors, alcohol is a kind of green and benign reagent that has been used in different biomass conversion reactions. This type of reagent is very convenient to use, and the involved operation process is safe, as compared to that of H2. In this review, the application of alcohols as liquid H-donors in the catalytic transfer hydrogenation of biomass-derived furanic compounds is depicted, and the representative reaction mechanisms are discussed. Emphasis is also laid on the selective control of product distribution in the described catalytic systems.
Keywords: catalytic transfer hydrogenation (CTH)